Mujahid al-Din Behrouz al-Khadim: His Life and Relationship with the Ayyubids - عبدالرحمان, عطا (Sulaimani Journal for Humanities, 2019)
The current study about the life of Mujahid-addeen Behrooz al-Khadim has been undertaken after studying many historical sources in Arabic and Kurdish languages. It shows the events that have led to expel him from his birthplace Dwīn and live in exile. However, he could use his intelligence and achieve the following there: 1) He could become so close to the Seljuks that he was entrusted the education of their princes and he used his intelligence to gain high ranks and posts. 2) Most of the occurrences of his name in the historical sources are related to his positive attitudes towards Shadi and later Najm ad-Dīn Ayyub and Asad ad-Dīn Sherko, the grandfather, the father and the uncle of Saladin respectively. 3) Mujahid-addeen Behrooz had a powerful personality, keen to work hard and persistent to develop the public life and administration despite the many times he was abdicated or stopped. However, every time, he was successful to come back to his posts and leave his clear fingerprints on the works he has undertaken. 4) He spent most of his time in Tikrit and he was implementing the orders of the SultanCaliph of Baghdad, orders such execution of the enemies of the Sultans or sending them to exile. He was entrusted even other important posts in other places such as Baghdad and Hilla. So, a foreigner (rumi) and a slave (mamluk) having reached such high and important posts without any real powerful supporter, except for his own intelligence and his own qualifications, is in fact admirable and deserves respect and high estimation.